The morphological response to the 13 May 2022 major explosive event at Stromboli volcano, Italy, characterised by high-resolution UAS surveys - Schmid, Markus; Kueppers, Ulrich; Ricci, Tullio; Civico, Riccardo; Cigala, Valeria; Fee, David; Gestrich, Julia E.; Iezzi, Alexandra M.; Cimarelli, Corrado; Vossen, Caron E. J.; Buzard, Richard M.; Ripepe, Maurizio; et al. (Volcanica, 2025)
Since 2019, the frequency of major explosive eruptions at Stromboli volcano (Italy) has increased, heightening the exposure of population and scientists to the hazards posed by ejecta. Morphological changes can directly alter the hazard potential associated with these phenomena. Here, we present a quantitative morphological analysis of changes of the crater terrace area linked to the 13 May 2022 major explosive event. High resolution (2.5 cm pixel-1) aerial imagery was acquired by unoccupied aircraft systems 2 hours before and 19 hours after the event. The 13 May 2022 major explosive event consisted of a minimum of seven explosions from four vents located in the south-central crater area. The opportune timing of this campaign enabled the quantification of morphological changes at Stromboli related to a single major explosive event at high temporal and spatial resolution. A total of 12.7 × 103 m3 was excavated and 5.5 × 103 m3 deposited. Via the mapping and classification of bomb distributions we observe that angular blocks make up the largest fraction of ballistics >0.2 m, from which we infer a strong interaction with wall rock and/or fragmentation of solidified plugs in the shallow plumbing system. The morphological changes observed provide valuable constraints on how much material is displaced, and the shift in location and the number of active vents during major explosive events at Stromboli.